Teacher’s education in remote education: what are we doing with ourselves at the university? (Research, Society and Development, 2022)
The present manuscript presents theoretical-practical articulations that intend to produce thinking based on the following problematization: what can university education in the context of a pandemic and what are we doing ourselves in this scenario? A university schooling today, having to deal with remote teaching from the same premises that had been used in face-to-face teaching, has been restricted to the fulfillment and operationalization of tasks, through different platforms and digital resources, causing exhaustion and production a micropolitics that depotentiates the cultivation of joyful affections in education. From a thread-writed, readers are invited to produce deflections from the compulsion of this process, consolidating themselves on the constitution of a collective gesture of narrating the minimal body, creating and strengthening moments that leverage the full exercise of presence in meetings, in construction of what we understand with a possible way of relating collectively, expanding insights of ethical conduct in the formation of Higher Education.